PIRIFORMIS SYNDROME - Hardi Adiyatma; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2022)
Abstract Piriformis syndrome is a disease characterized by inflammation of the peripheral nerves in the sciatic nerve caused by abnormal conditions in the piriformis muscle. Piriformis syndrome is caused by excessive or excessive contraction of the piriformis muscle. Piriformis syndrome is underdiagnosed and considered as common back pain and causes 6% of similar symptoms to Low Back Pain (LBP) and the incidence rates in LBP patients varying, from 5% to 36%. The incidence of PS is about 2.4 million new cases each year and it is more common in women than men. Piriformis syndrome usually happened in the 4th and 5th decades of life. There are various variations of the relationship between the sciatic nerve and the piriformis muscle where this anatomical shape is a risk factor for piriformis syndrome. The diagnosis of piriformis using functional (Fair Test, Beatty Maneuver, Modified Beatty Maneuver, Pace Test, Freiberg Test, Braggard Test, Straight Leg Raise Test, Bonnet Test, Micrine Test) and imaging modalities (USG, EMG, CT-Scan, MRI). The management of piriformis syndrome is carried out in the order of warning management, medical management, physical therapy, steroid spraying, botulinum spraying, and surgical technique. The prognosis of piriformis syndrome depends on the severe condition of each patient, a study reports that even patients who have undergone surgery can still get piriformis syndrome again Keyword : Piriformis syndrome, piriformis muscle, functional tests, management